1985
DOI: 10.1002/ajh.2830190414
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella infection in hairy cell leukemia: Report of a case

Abstract: A patient with hairy cell leukemia who developed mediastinal mass and fever is described. A CT-guided aspiration of the mass yielded Salmonella tiphymurium. Granulocyte response to infection was intact and could explain the favorable course of this unusual Salmonella infection. Although several reports deal with salmonellosis as a complication of immunodeficiency states, this type of infection is of rare occurrence in hairy cell leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…almonella infection occurs through fecal-oral transmission and usually appears in the biliary tract in the rare instance that it is extraintestinal. Thoracic Salmonella infection is rare [1][2][3] and has never been reported in the thymus. One case attributes a Salmonella thyroid abscess to the immunosuppressive therapy for myasthenia gravis.…”
mentioning
confidence: 99%
“…almonella infection occurs through fecal-oral transmission and usually appears in the biliary tract in the rare instance that it is extraintestinal. Thoracic Salmonella infection is rare [1][2][3] and has never been reported in the thymus. One case attributes a Salmonella thyroid abscess to the immunosuppressive therapy for myasthenia gravis.…”
mentioning
confidence: 99%
“…To the best of our knowledge, there are limited reports on this rare association. 2,7,8 In early eighties Marsh et al 7 reported probabably the first case of salmonella mediastinitis in a patient who presented with fever and chest pain. Radiology revealed mediastinal mass, and mediastinotomy and culturing aspirate from the mass showed growth of salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 12 cases of Salmonella mediastinal infection have been reported, including this current case (Table 1). Only three cases occurred in the absence of preexisting tissue disruption: one patient was on immunosuppressive agents and had exposure to chickens [4], the second had hairy cell leukemia [5], and the third was immunocompetent but had recently sustained a facial bite from a raccoon [6]. Four cases were reported demonstrating NTS infection of abnormal thoracic tissues, including NTS abscess development within known [7–9] or suspected [10] thymomas.…”
Section: Discussionmentioning
confidence: 99%